The poetic image in the collection of poems (Abu Al-Shaqmaq): a critical and analytical study - Marouf, Dr. Tishkek Othman Arif Marouf (Sulaimani Journal for Humanities, 2025)
This study belongs to the field of studies that prepared the text with a linear structure that creates both an aesthetic and a semantic effect, with the recipient interacting with the text produced by the poet or a writer, because the text is reborn with multiple readings and different interactions with it. In this sense, the study selected: The poetry image in the Diwan (Abi al-Shamqeq) is an analytical critical study, because of the importance of the poetry image in the formation of systems on the one hand and beauty on the other, The process of selecting, inspiring and transmitting these images in a poetic form, urgently needs to study, analyses and scrutinize the poet's intentions and the motives, causes or ends that led to this process. The circumstances surrounding the process of poetic systems or production of poetry, the sources of poetry images that existed and were present in his time, How the poet shares problems, obstacles and concerns surrounding members of society, whether political, economic, ideological or religious and transposed this psychological and emotional experience into a poetic experience filled with contradictory sensations, mixed feelings and differing experiences, aesthetically influencing the recipient.
Keywords: Sources of poetic images; image; Abu AlShaqmaq; contents of poetic images; irony